Associated Factors with Erectile Dysfunction in Hemodialysis Patients at Dr. Reksodiwiryo Hospital Padang - Vidiansyah, Achmad; Putra, Mindy Pasuma; Veronike, Evelin; Harun, Harnavi (PERNEFRI (PERHIMPUNAN NEFROLOGI INDONESIA), 2025)
Background: Erectile dysfunction (ED) is a common condition affecting a significant number of men worldwide, with its prevalence particularly high among patients with chronic kidney disease (CKD). Objective: This study aims to investigate the association between ED and CKD in patients undergoing hemodialysis. Methods: This study used a survey approach, designed with cross-sectional involving 24 male patients undergoing hemodialysis at the hospital from January to July 2024. Data were gathered using the IIEF-5 questionnaire as well as patient records. The severity of ED was classified based on IIEF-5 scores, and data analysis was conducted using SPSS. Results: Most respondents (58.3%) were under 60 years old, with 58.3% having hemoglobin levels below 10 g/dL and 79.2% with a KT/V ratio under 1.8. ED prevalence was high at 95.8%, with severe ED affecting 54.2%. A significant correlation existed between KT/V and ED severity p<0.05, while hemoglobin levels showed no significant association p>0.05. The high prevalence of ED in CKD patients undergoing hemodialysis highlights the importance of regular screening and early intervention. The study indicates that sufficient hemodialysis, as measured by the Kt/V ratio, could be essential in reducing the severity of ED in this group. However, hemoglobin levels did not show a significant connection to ED severity, which contrasts with certain earlier research findings. Conclusion: Erectile dysfunction is common among CKD patients undergoing hemodialysis, with insufficient dialysis being a key contributing factor. This highlights the need to maintain adequate dialysis to reduce the severity of ED in these individuals.